Realistic Monte Carlo simulation of the INOR Therapy Unit and electron contamination calculation for a board 60Co Beam - J. Ernesto Mainegra; Roberto Capote (Tecnología en Marcha)
The therapy beam from the 60Co unit used at INOR was modeled using the EGS Monte Carlo radiation transport system. The rectangular geometry of the collimating system is fully simulated and the effect of considering the outer collimator a set of stepped collimators rather than a collimator with a smooth surface was estimated. Variance reduction techniques are widely used to increase the efficiency of our calculations. Even for the dose at very shallow depths (<0.5 mm) the agreement of our calculations with the experimental results is very good. The shift of peak dose to about 1 mm due to electron contamination is observed.